Koch and al-Attas on solitary freedom: an analysis of Bryce Andrews’s ranch memoir - Mohd Zaimin Haris Fathillah,; Ravichandran Vengadasamy, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Solitude has gained attention lately due to the growing emphasis on mental and emotional health. Freedom is one of the fundamental aspects of solitude. This study comparatively explores the concept of solitary freedom in Bryce Andrews’s ranch memoir through the distinct perspectives of Philip Koch and Syed Muhammad Naquib al-Attas. While literary studies increasingly acknowledge the significance of solitude and its connection to freedom, there remains a gap in exploring how diverse philosophical traditions, particularly Islamic understandings of freedom, inform the theme of solitary freedom within Ranch Literature. To address this, the study examines Andrews’s work by first employing Koch’s features of freedom to detail experiences related to solitude. It then comparatively interprets these categories through the lens of al-Attas’s Islamic outlook on freedom. Through a content analysis of textual evidence expressing solitude, the findings reveal complementary aspects of how Koch and al-Attas illuminate solitary freedom in Andrews’s ranch-themed work. This paper responds to the need to heighten interdisciplinary awareness, as well as enabling inter-discourse studies of literature and Islamic philosophy.